2019
DOI: 10.1186/s12245-019-0235-x
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary in situ simulation-based medical education in the emergency department of a teaching hospital in Nepal

Abstract: Background Simulation is well established as an effective strategy to train health care professionals in both technical and nontechnical skills and to prevent errors. Despite its known efficacy, adequate implementation is restricted due to the financial burden in resource-limited settings like ours. We therefore pursued to introduce cost-effective in situ simulation (ISS) in the emergency department (ED) to explore its impact on perception and learning experience among multidisciplinary health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 16 publications
0
40
0
1
Order By: Relevance
“…Experiential learning, deliberate practice and the ability to provide immediate feedback are the primary advantages of simulation-based medical education. It is an effective way to develop new skills, identify knowledge gaps, reduce medical errors, practice teamwork communication and maintain infrequently used clinical skills with the overall goal of improving patient care [6]. Although simulation cannot replace clinical exposure as a form of experiential learning, it replicates real life situation and promotes learning without compromising patient safety.…”
Section: Resultsmentioning
confidence: 99%
“…Experiential learning, deliberate practice and the ability to provide immediate feedback are the primary advantages of simulation-based medical education. It is an effective way to develop new skills, identify knowledge gaps, reduce medical errors, practice teamwork communication and maintain infrequently used clinical skills with the overall goal of improving patient care [6]. Although simulation cannot replace clinical exposure as a form of experiential learning, it replicates real life situation and promotes learning without compromising patient safety.…”
Section: Resultsmentioning
confidence: 99%
“…Our project resonates with other studies looking at the use of in situ simulation to improve staff confidence level and teamwork skills. It also offers an opportunity to test the introduction of protocols, guidelines, and system changes, while observing for latent safety threats to their introduction and possible solutions [9].…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that ISS provides a unique opportunity to increase the confidence level and skills of multidisciplinary staff which was also demonstrated in our previous study. 20 Our previous experience with such pandemics was scarce. We had limited time to prepare for the increased surge of the suspected cases and safety of our staff was the major concern.…”
Section: Discussionmentioning
confidence: 99%
“…The simulations were conducted by the ED faculties who had past trainings and experience in conducting simulations. 20,29,30 For triage ISS, we designed case scenarios of the patients arriving in the ED falling under different triage categories (Supplement 3a). The triage personnel interviewed the simulated patients (SiP) portraying various case scenarios and the participants had to allocate the SiP to the appropriate zones ( Figure 3).…”
Section: Study Procedures and Data Collection Toolsmentioning
confidence: 99%
See 1 more Smart Citation